Desain Metode PID-Simulated Annealing Sebagai Kontrol Temperatur Pada Inkubator Bayi - Yoga Alif Kurnia Utama; Dwi Taufik Hidayat (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2020)
This study compares 2 controllers, the On-Off controller and the PID-Simulated Annealing which is a PID control whose parameters are tuned using the simulated annealing method. Both methods are applied to the incubator accompanied by 3 disturbances in the form of variations in the outside air temperature which affect the temperature inside the incubator. The performance of the two controllers is calculated using the Integral Time Absolute Error (ITAE) criteria. The results showed that the average ITAE between On-Off and PID-Simulated Annealing controls was 534,925 and 1,894. These results it can be concluded that the PID-Simulated Annealing control is the most effective control in regulating the temperature of the air inside the incubator and can maintain the air temperature from interference due to outside air temperatures.